Covalent-reversible peptide-based protease inhibitors. Design, synthesis, and clinical success stories - Feral, Anthony; Martin, Anthony R.; Desfoux, Alexandre; Amblard, Muriel; Vezenkov, Lubomir L. (Amino acids, 2023)
Dysregulated human peptidases are implicated in a large variety of diseases such as cancer, hypertension, and neurodegeneration. Viral proteases for their part are crucial for the pathogens’ maturation and assembly. Several decades of research were devoted to exploring these precious therapeutic targets, often addressing them with synthetic substrate-based inhibitors to elucidate their biological roles and develop medications. The rational design of peptide-based inhibitors offered a rapid pathway to obtain a variety of research tools and drug candidates. Non-covalent modifiers were historically the first choice for protease inhibition due to their reversible enzyme binding mode and thus presumably safer profile. However, in recent years, covalent-irreversible inhibitors are having a resurgence with dramatic increase of their related publications, preclinical and clinical trials, and FDA-approved drugs. Depending on the context, covalent modifiers could provide more effective and selective drug candidates, hence requiring lower doses, thereby limiting off-target effects. Additionally, such molecules seem more suitable to tackle the crucial issue of cancer and viral drug resistances. At the frontier of reversible and irreversible based inhibitors, a new drug class, the covalent-reversible peptide-based inhibitors, has emerged with the FDA approval of Bortezomib in 2003, shortly followed by 4 other listings to date. The highlight in the field is the breathtakingly fast development of the first oral COVID-19 medication, Nirmatrelvir. Covalent-reversible inhibitors can hipothetically provide the safety of the reversible modifiers combined with the high potency and specificity of their irreversible counterparts. Herein, we will present the main groups of covalent-reversible peptide-based inhibitors, focusing on their design, synthesis, and successful drug development programs.